EVALUATION OF BUFFALO BULL SPERMATOZOAL DNA DAMAGE USING SINGLE CELL GEL ELECTROPHORESIS: Life Sciences-Veterinary Science - NANDRE, RAHUL; DERASHRI, HARESH; JOSHI, CHAITANYA (International Journal of Life Science and Pharma Research, 2011)
Deoxyribonucleic acid was influenced by sperm ageing and sperm storage temperature. In this study, the effect on DNA integrity at pre-freeze and post-freeze stages was analyzed by single cell gel electrophoresis during winter and summer seasons. Traditionally, the diagnosis of male infertility depends on microscopic assessment and biochemical assays to evaluate quality of semen. These tests are needed to provide the basic information for initial diagnosis. However, none of these parameters gives information about sperm function and their fertilization capability. The fertility of these sperms is questionable. The evaluation of sperm DNA damage is a promising technique to diagnose the male infertility. It has been shown to be closely associated with negative relationships with fertilization, embryo quality, implantation and positive relationships with abortion. Here we report the effect of preservation temperature and season on sperm DNA damage, using the single cell gel electrophoresis to measure DNA fragmentation. The significant difference (P<0.05) in DNA damage among Surti buffalo bulls spermatozoa were more pronounced at post-freeze stage as compared to the pre-freeze stage. In addition, the significant difference (P<0.05) in DNA damage was observed among Surti buffalo bulls spermatozoa during summer season as compared to the winter season. The changes on DNA integrity were dependant on temperature of preservation, period of storage and seasonal variation. The single cell gel electrophoresis can be used to detect low levels of DNA damage in Surti buffalo bulls spermatozoa. Therefore, screening of the sperm DNA damage may be used as an additional test of sperm quality that can have diagnostic importance in the male infertility.